The dune and the forest: contemporary landscape design in light of Mcharg's ecological view - Olivo, Carla; Meneguetti, Karin (Paisagem e Ambiente, 2023)
Complexity and simplification, diversity and uniformity, instability and stability, are dualities employed by Ian McHarg in Design with nature to present his naturalistic view: fitting and creative in character. Such terms remain central to the writing of landscape architecture theory in times of the Anthropocene, regarding the fact that environmental issues are not new, but are increasingly urgent. From that assumption, considering the expanded paradigm of landscape ecology as well, this paper aims to discuss in a theoretical and conceptual way the design as a tool, reflecting on the implications of the inclusion of the environmental adjective. Therefore, this paper reviews leading authors in a global perspective, assessing revised understandings and transdisciplinary concepts, especially ecological-based and cultural-based. It proposes the design of a conceptual framework to comprehend environmental design, arranged into design concepts.